General Anestesi Intravena pada Tindakan Debridement dan Tangensial Eksisi Pasien Combustio 13.5% Grade Iia - Dila Khairunnisa Mahira Zulmay; Abrar Abrar (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
It was reported that the patient, a 40 year old woman, weighing 53 kg, would undergo debridement and tangential excision. The patient said he had no history of previous illness. The patient also denied a history of allergies and dentures. The patient also does not currently have a cold, cough or fever. Therefore, the patient is classified as ASA I because he has no systemic abnormalities. In this operation, an intravenous general anesthesia technique was used because the duration of the surgery is not long, and it also avoids the effects of inhalation sedation. The patient did not use respiratory assistance and had strict intraoperative monitoring to maintain airway patency.The drugs used are midazolam and fentanyl as pre-medication, and propofol as an induction drug, which is then treated with propofol intermittently. After the operation is complete, the patient is immediately transferred to the recovery room, and his consciousness value is checked using the Aldrette score, which in this patient's score is 10, and therefore, the patient can be transferred to the treatment room.